Analysis of The Multifunctional Economic Value of Rice Field As Producers of Cultivation Media and Products/ Environmental Services in Sidoarjo District, East Java Province, Indonesia Year 2024 - Markus Patiung; Nugrahini Susantinah Wisnujati (Postgraduate, University of Mataram, 2024)
Rice fields managed by farmers or agricultural business actors provide cultivation benefits and environmental services. Research in Japan shows that the environmental benefits of rice fields reach 90%, much higher than its role as a cultivation medium which is only 10%. This study aims to examine the economic value of rice fields as a whole in three main aspects: (1) its value as a rice field medium, (2) its value as an environmental service, especially flood control, and (3) a comparison of these economic values. The method used is economic valuation through the Replacement Cost Method (MBP) and the calculation of farming profits. MBP is used to calculate the economic value of rice fields that do not yet have a market price. Meanwhile, the calculation of farming profits is to assess the cultivation benefits produced by rice fields. The results of the study show that (1) the economic value of rice fields as a rice field medium is IDR 24,750,000 per hectare per year. (2) As a provider of flood control, its economic value reaches IDR. 150,276,000 per hectare per year, and the conversion of 350 hectares could result in an annual loss of Rp. 52.6 billion. (3) The comparison of the economic value between rice fields as a planting medium and as a flood controller is 1:6, highlighting the important environmental benefits provided by rice fields